Attitudes and role orientations on doctor-patient fit and patient satisfaction in cancer care - Chan, C.M.; Azman, W.A. (2012)
INTRODUCTION: Findings in the area of patient-physician relationship are riddled with inconsistencies. Although patient-centredness has been found to have special relevance in chronic illnesses, no study in the Southeast Asian region has so far examined role orientation and its implication for patient-centred outcomes in the cancer context. This study aimed to examine role orientation in cancer patients and their physicians, doctor-patient fit and how this congruence relates to patient satisfaction. METHODS: The participants were 80 cancer patients and 12 physicians from a single academic medical centre. All participants completed the Patient-Practitioner Orientation Scale, while only the patient participants completed the self-administered Patient Satisfaction Questionnaire. RESULTS: The cancer patients and their oncologists were found to be patient-centred and thus showed a high doctor-patient fit. Our findings also support the hypothesis that patient-centredness (overall mean = 4.66 ± 0.585) and patient-physician congruence (overall mean = 4.95 ± 0.088) are significantly associated (t(90) = -1.75, p = 0.084) with patient satisfaction (r = 0.56, p < 0.01). CONCLUSION: To our knowledge, this study is the first in the Southeast Asian context to examine congruence using role orientations of cancer patients and their oncologists as well as the resultant patient satisfaction in an actual clinical setting. The finding that strong doctor-patient fit is linked to higher patient satisfaction is unexpected and differs from the results of other studies from the USA. Further studies are required in order to examine how this may be influenced by differences in socio-cultural norms and expectations.